Calretinin expression as a reliable prognostic marker in different molecular subtypes of breast carcinoma - Mayada Saad Farrag; Amro Awad El-karef; Maha Mohammed Amin; Nagwa Mokhtar Helal; Omar Farouk Ali; Nesrine Saad Farrag (Wolters Kluwer Medknow Publications, 2017)
Background: Calretinin (CR), a known mesothelial marker, is expressed in both epithelial and mesenchymal malignancies including breast cancer. Aims: We aimed to measure the frequency of CR expression in correlation with other clinicopathological parameters of different molecular subtypes of invasive breast carcinoma and to study its prognostic implications in this common cancer.Study Design: Tissue microarrays were constructed from 225 tissue samples of breast carcinoma cases. Subjects and Methods: Immunostaining for CR in addition to estrogen receptors, progesterone receptors, human epidermal growth factor receptor 2 (HER2), epidermal growth factor receptor, CK5/6, and Ki-67 for molecular subtyping. Statistical Analysis Used: Chi-square and Fisher's exact tests were done using SPSS 18.0 software (IBM Inc.). Survival data were analyzed using Kaplan-Meier test, Log-rank test, and Cox proportional hazard models. Results: Cases of invasive breast carcinomas with different grades were classified into 84 luminal A, 45 luminal B, 27 HER2 positive, 40 basal-like, and 29 unclassified. High CR expression was associated with tumors of high grade (P < 0.0001), high locoregional recurrence (P = 0.005), hormonal receptors negative, and high Ki-67 indices. They frequently display a basal-like phenotype (70%, P < 0.0001), HER2 (59.3%), and luminal B (33.3%) tumors compared to luminal A (9.5%) and unclassified subtypes (17.2%). Moreover, it is associated with poor overall patient survival (P = 0.034), but it does not affect disease-free survival. Conclusions: Calretinin could be a reliable predictor marker of adverse prognosis in breast cancer.